The Influence of Performance Effectiveness, Procedural Justice and Social Capital on Public Trust In The Police In The Central Jakarta Metro Police Jurisdiction - Rusliwa Somantri, Gumilar; Robet, Robertus; Hendriyana, Hendriyana (Green Publisher Indonesia, 2024)
Public trust in the police is a problematic issue for modern police everywhere, including in Indonesia. The police agency needs a high level of trust to be able to carry out its duties and functions as the person in charge of social order and law in society. This study intends to examine the influence of performance effectiveness, procedural justice and social capital on public trust in the police in Central Jakarta. The survey was conducted to 400 respondents using the cluster purposive random sampling method at the sub-district level. The results showed that the performance effectiveness variable had a significant effect (0.275), the procedural justice variable had no significant effect, and the social capital variable had a significant effect (0.133). The awareness of the importance of trust has been observed by the National Police leadership since the National Police institution was officially separated from the ABRI. In this case, the National Police formulated a bi-annual Grand-Strategy covering the period 2005-2025, as a step to encourage systematic organizational change towards the National Police as a professional modern police force.